OTFTs using hybrid films as gate dielectrics prepared via UV curing and sol-gel reaction - Choi, June Whan; Yoon, Ho Gyu; Kim, Jai Kyeong (ELSEVIER SCIENCE BV, 2010)
The work presented here focuses on the preparation and characterization of gate dielectrics in organic thin-film transistors (OTFTs), fabricated by the sol-gel process. Hybrid dielectrics were prepared with acryl UV resin, titanium n-butoxide, catalytic HCl, and acetylacetone by sol-gel process and patterned by UV cross-linking below 120 degrees C. Leakage currents of dielectric layers remained below 10 (9) A under operating voltage and dielectric constants were measured to be similar to 6.5 at 10 kHz. The field effect mobility and on-off ratio were similar to 0.86 cm(2)/V s and similar to 10(4), respectively. These results demonstrate that sol-gel hybrid systems are suitable for gate dielectrics in OTFTs. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: LOW-VOLTAGE; ORGANIC TRANSISTORS; INSULATOR